UDP-Glucose: A Potential Signaling Molecule in Plants? - Janse van Rensburg, Henry Christopher; Van den Ende, Wim (Frontiers in Plant Science, 2018)
This perspective paper focuses on the most recent results suggesting a potential role for UDP-Glucose as a signalling molecule in plants. In animals, UDP-Glucose is well established as an extracellular signalling molecule that is sensed by G-protein coupled receptors, activating several downstream defence mechanisms. Recent studies have shown that abnormal growth occurred in both vegetative and reproductive tissue of plants with reduced UDP-Glucose levels, and this could be rescued by exogenous UDP-Glucose. In plants with increased biomass accumulation, the genes involved in UDP-Glucose production were up-regulated. However, excessive endogenous accumulation of UDP-Glucose induced programmed cell death, and this could also be obtained by exogenous UDP-Glucose application. Plants with decreased UDP-glucose were insensitive to pathogen induced programmed cell death. We speculate that UDP-Glucose acts as an extracellular signalling molecule in plants, and that it may be perceived as a damage-associated molecular pattern (DAMP).